Interfirm Adoption of Capital-Goods Innovations - Benvignati, Anita M. (The Review of Economics and Statistics, 1982)
The diffusion of industrial technology through its principal agents (firms) can have far-reaching effects on factor productivity, economic growth, and inflation in a market-oriented economy. Because of this, studies have sought to discover the conditions most favorable to technically-progressive decisions by individual firms. This paper, by exploring some important empirical relationships affecting the propensity of American textile mills to purchase textile machinery innovations in the postwar period, offers the opportunity to discover additional insights into the area from a new and extensive body of industry data, as well as to verify (or disavow) some earlier findings where economists have had only limited observations and industries to study. Moreover, a unique exposure to the process is provided by conducting an examination of a traditional, fragmented industry rather than the usual hightechnology, capital-intensive industry. The analysis begins by relating some important economic attributes of firms to decisions regarding adoption, and the timing of adoption, of thirty-three textile machinery innovations. The often dominating firm-size factor is examined along with the firm's competitive environment, its labor costs, and its foreign activity involvement. The paper then estimates the concentration of progressive behavior in textiles to determine if the same firms have repeatedly been the pioneers. This concentration is contrasted with experiences established in other industries. Finally, the timing of overall industry adoption is related to the industry's business cycle, to determine where in the cycle it is typical for firms to proceed with modernization efforts.